Relative validation of a food frequency questionnaire for national health and nutrition monitoring - Haftenberger Marjolein (Nutrition Journal, 2010)
Abstract Background Validation of a food frequency questionnaire (FFQ) is important as incorrect information may lead to biased associations. Therefore the relative validity of an FFQ developed for use in the German Health Examination Survey for Adults 2008-2011 (DEGS) was examined. Methods Cross-sectional comparisons of food consumption data from the FFQ and from two 24-hour recalls were made in a sample of 161 participants (aged 18 to 80 years) of an ongoing nationwide survey, the German National Nutrition Monitoring (NEMONIT). The data collection took place from November 2008 to April 2009. Results Spearman rank correlations between the FFQ and the 24-hour dietary recalls ranged from 0.15 for pizza to 0.80 for tea, with two third of the correlation coefficients exceeding 0.30. All correlation coefficients were statistically significant except those for pizza and cooked vegetables. The proportion of participants classified into the same or adjacent quartile of intake assessed by both methods varied between 68% for cooked vegetables and 94% for coffee. There were no statistically significant differences in food consumption estimates between both methods for 38% of the food groups. For the other food groups, the estimates of food consumption by the FFQ were not generally higher or lower than estimates from the 24-hour dietary recalls. Conclusions The FFQ appears to be reasonably valid in the assessment of food consumption of German adults. For some food groups, such as raw and cooked vegetables, relative risks estimates should be interpreted with caution because of the poor ranking agreement.